Theory of energy transforming systems and their application in diagnostics of operating systems - Cempel, Czesław (Zielona Góra: Uniwersytet Zielonogórski)
In this paper the theory of energy transforming systems (ETS) with finite dissipation capacity was presented and applied to condition assessment of operating systems (OS). It was shown that externally dissipated energy transformed into life-symptom of OS has direct equivalence with its reliability, and the remaining life. It was shown also, that ETS modules can serve as building block for creating the diagnostic and reliability models of any OS.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka